Transformasi Struktur Pekerjaan dan Kebutuhan Keterampilan di Era Teknologi AI dan Otomatisasi di Pasar Global - Izzatul Mula; Auliya Ristiani (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The era of AI and automation technologies has fundamentally changed the structure of jobs and skill needs in the global market, driving significant transformation in the digital business world. This research aims to analyze the impact of these technological developments on the jobs and skills required by the modern workforce. Using the literature review method, this research evaluates various academic sources and related industry reports. The findings show that there is a shift away from routine work towards jobs based on analytical, creative and interpersonal skills, with a growing demand for expertise in data management, programming and emotional intelligence. In addition, the research reveals a significant skills gap, which could exacerbate socio-economic inequality if not addressed. The implications of this study emphasize the importance of investing in retraining and workforce skills development to support adaptation to technological transformation, as well as the need for collaboration between government, educational institutions and industry in designing inclusive and sustainable policies.